Anatomy, Morphometry and Radiography in the thoracic limb bones of the Patagonian Huemul Deer (Hippocamelus bisulcus). (23rd March 2020) - Salinas, Paulo; Núñez‐Cook, Samuel; Arenas‐Caro, Abigail; Moreno, Luis; Curihuentro, Escarlet; Vidal, Fernando
Abstract: The aim of this study was to provide morphometric, anatomic and radiographic data of the thoracic limb bones of the Patagonian Huemul ( Hippocamelus bisulcus ) including a functional interpretation of this, as a reference for clinical use, biomedical research and teaching purposes. Currently, the Patagonian huemul deer is in danger of becoming extinct due to multiple causes. Research carried out for its conservation has focused mainly on its ecology and pathology, leaving gaps in biological knowledge, which is basic and important for its comprehension. This study was conducted to reveal the gross osteology and radiology features of the thoracic limb bones of the Patagonian huemul deer. The osteological findings suggest the presence of powerful flexor muscles in the scapulohumeral and elbow joints, useful to cushion the jumps. Also, the principal nutrient foramen of Patagonian huemul differs in position with respect to domestic ungulates, which may be important to consider during surgical procedures. Finally, the radiographic data can provide new information about the tissue loading conditions in Patagonian huemul, so that this new knowledge can be of great importance for a better understanding of mechanically induced or adaptive changes in bone produced by habitat or other ecological phenomena.